(untitled) (Bulletin KNOB, 2011)
Before the construction of a car park in 2007 a flooded medieval church with graveyard was excavated a few kilometres south of the town of Dordrecht. Part of the roof of a medieval village church emerged. On the exterior of this church part of the original slating had been preserved. The wood of the roof was dendrochronologically dated around 1350. The church was lost during the St Elizabeth flood of 1421. It concerns an original, extremely rare combination of roof boards with slate. The high-pitched roof boards were supported by rafters and through spur ties and slabs they stood on the masonry by means of ashlar pieces. Behind the rafters and (presumably existing) trusses, counter braces ran in a V-shaped pattern. The slates are different in shape, but the covering shows most resemblance to that of the Rhine slates. An XRF analysis by RCE Amersfoort appears to indicate that the slates came from Fumay in northern France, a well-known quarry for slate.